Numerical investigation on the strength of different types of adhesively bonded lap joints. (2023) - Boban, A.; Kurian, S.; Pooppally, T.J.; Kumar, R.R.; Gaur, P.; Singh, D.
Abstract: In recent years, adhesively bonded joints are extensively used in a multitude of technological applications, mainly in industries such as aerospace and automobile. Adhesive bonding is often chosen over other joining techniques like bolting, riveting as well as welding, due to the reduction of stress concentrations, easy manufacturing and reduced weight penalty, amongst other issues. For the investigation of the behavior of adhesive bonded joints, the stress–strain behavior of the structural adhesive is necessary. The present study aims to investigate the strength of various types of adhesively bonded lap joints by using the commercial finite element tool ANSYS. It is seen from the analysis that the double lap joint is the type of joint which is least affected by the forces acting on it followed by the single step lap joint.